Influence of Murraya koenigii extract on diabetes induced rat brain aging - Bhupatiraju, Lakshmi; Bethala, Krupavaram; Goh, Khang Wen; Dhaliwal, Jagjit Singh; Siang, Tan Ching; Shasidharan, Menon; Bama, V.V. Menon; Kishore, Babu Anchu; Chan, Siok Yee; Long, Chiau Ming *; Khan, Abdullah (Jurnalul Pentru Medicina Si Viata S.R.L., 2023)
Food supplements are used to improve cognitive functions in age-related dementia. This study was designed to determine the Murraya koenigii leaves’ effect on Alloxan-induced cognitive impairment in diabetic rats and the contents of oxidative stress biomarkers, catalase, reduced glutathione, and glutathione reductase in brain tissue homogenates. Wistar rats were divided into seven groups (six rats per group). Group I received saline water (1 ml, p.o.), Diabetes was induced in Groups II–VII with Alloxan (120 mg/kg/p.o). Group III was provided with Donepezil HCl (2.5 mg/kg/p.o.), Group IV, V, VI, and VII with Murraya koenigii ethanol extract (200 and 400 mg/kg/p.o.) and aqueous extract (200 and 400 mg/kg/p.o.), respectively, for 30 days. Behavior, acetylcholinesterase (AChE) activity, oxidative stress status, and histopathological features were determined in the hippocampus and cerebral cortex. Administration of Murraya koenigii ethanolic and aqueous extracts significantly (P<0.05, P<0.001) increased the number of holes crossed by rats from one chamber to another. There was an increase in the (1) latency to reach the solid platform, (2) number of squares traveled by rats on the 30th day, and (3) percentage of spontaneous alternation behavior compared to the control group. Administration for successive days markedly decreased AChE activity (P<0.05), decreased TBARS level, and increased catalase, GSH, and GR levels. Murayya koenigii could be a promising food supplement for people with dementia. However, more research into sub-chronic toxicity and pharmacokinetic and pharmacodynamics interactions is essential.